Generation of 3-deoxypentulose by the isomerization and β-elimination of 4-O-substituted glucose and fructose. (October 2021) - Chiku, Kazuhiro; Yoshida, Mitsuru; Ono, Hiroshi; Kitaoka, Motomitsu
Abstract: Aldose–ketose isomerization is commonly used to prepare rare oligosaccharides such as maltulose (4- O -α-d -glucopyranosyl-d -fructose) and lactulose (4- O -β-d -galactopyranosyl-d -fructose). However, both sugars are degraded under alkaline conditions via β-elimination, while their subsequent benzylic acid rearrangement leads to the formation of isosaccharinic acids. Here, we investigated the behavior of maltose and maltulose upon heating in phosphate buffer solution at pH 7.5. Maltose was initially isomerized into maltulose. Maltulose was degraded via β-elimination, followed by keto–enol tautomerization, which led to the formation of a 1, 3-dicarbonyl intermediate bearing an aldehyde group at the C-1 position and a ketone group at the C-3 position. Subsequent hydrolysis of this intermediate afforded formic acid and 3-deoxy-d - glycero -pent-2-ulose (1 ) as the major products based on HPLC and NMR data. In contrast, the formation of isosaccharinic acid via benzylic acid rearrangement, not the 3-deoxypentulose, was reported under the strongly alkaline conditions (Knill and Kennedy, 2003). The heat treatment of 1→4 linked oligo- and polysaccharides possessing glucose or fructose residue at the reducing end under neutral pH conditions could be applied for the practical preparation of a 3-deoxypentulose. Graphical abstract: Image 1 Highlights: 3-Deoxy-d - glycero -pent-2-ulose (1 ) was formed upon heating of maltose at neutral pH. The reaction mechanism involved aldose–ketose isomerization and β-elimination. Compound 1 was found in acyclic chain and furanose forms in aqueous solution. Compound 1 was not formed under strong alkaline conditions. Saccharides bearing 4- O -substituted glucose and fructose can form 3-deoxypentulose.